Efficacy of topical galbanum oil with dry cupping in hospitalized COVID-19 patients: A randomized open-label clinical trial - Fateme Seydi; Mohammadreza Salehi; Fataneh Hashem-Dabaghian; Fatemeh Emadi; Mohammad Gholami-Fesharaki; Maryam Iranzadasl (Avicenna Journal of Phytomedicine, 2023)
Objective: This study was designed to detect the therapeutic effects of galbanum oil plus dry cupping (a Persian medicine-based method) in hospitalized patients with coronavirus disease-2019 (COVID-19).Materials and Methods: In this randomized controlled trial, 60 hospitalized COVID-19 patients with positive polymerase chain reaction test (PCR), pulmonary involvement and blood oxygen saturation (SpO2) ≤93 mmHg, were randomly assigned into two groups to take the standard therapeutic regimen alone or alongside cupping and topical galbanum oil (Ferula gommosa oleo-gum resin) for 3-5 days. The SpO2 level, the severity of signs and symptoms of patients and laboratory parameters were compared between the two groups.Results: Fifty-eight patients were analyzed. The SpO2 level changed from 89.27±3.82 to 90.29±3.09 mmHg (p=0.038) in control group, while it increased from 88.74±3.45 to 94.23±2.1 mmHg (<0.001) in galbanum group with a significant difference between the groups (p<0.001). Fever, cough, dyspnea, and anorexia alleviated in the galbanum group more than the control (p=0.003, 0.001, 0.01, and 0.04, respectively). No adverse effects were reported due to galbanum oil and cupping therapy.Conclusion: Dry cupping with galbanum oil alongside the routine therapeutic regimen could be more effective than the routine therapeutic regimen alone for improving SpO2 level and alleviating fever, cough, and dyspnea in COVID-19 patients.